The Role of Managerial Ability in Corporate Tax Avoidance - Koester, Allison; Shevlin, Terry; Wangerin, Daniel (Management science, 2017)
Most prior studies model tax avoidance as a function of firm-level characteristics and do not consider how individual executive characteristics affect tax avoidance. This paper investigates whether executives with superior ability to efficiently manage corporate resources engage in greater tax avoidance. Our results show that moving from the lower to upper quartile of managerial ability is associated with a 3.15% (2.50%) reduction in a firm’s one-year (five-year) cash effective tax rate. We examine how higher-ability managers reduce income tax payments and find that they engage in greater state tax planning activities, shift more income to foreign tax havens, make more research and development credit claims, and make greater investments in assets that generate accelerated depreciation deductions. Identifying a manager characteristic related to firms’ tax policy decisions adds to our understanding of the factors that explain the substantial variation in corporate income tax payments across firms. This paper was accepted by Mary Barth, accounting .